2014
DOI: 10.1159/000358013
|View full text |Cite
|
Sign up to set email alerts
|

Functional Closure of the Ductus Arteriosus at Birth: Evidence against an Intermediary Role of Angiotensin II

Abstract: The fetal ductus arteriosus (DA) closes postnatally first functionally and then structurally. Normal rise in blood oxygenation is regarded as a prime trigger, but closure may occur more slowly without this stimulus. Here, our aim wasto assess the role of angiotensin II (Ang II) in functional closure of DA since its action may not be conditioned by oxygen. Experiments were performed with wild-type fetal and neonatal mice, using whole-body freezing technique to assess DA caliber in vivo. Transcripts for Ang II t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…They exert their anti-inflammatory effects through the inhibition of endogenous prostaglandins. Similar effects have been reported with black tea, resveratrol, mate tea, orange juice and dark chocolate ( 207 ). Excessive consumption of such foods by the pregnant woman may influence the dynamics of the DA, by inhibiting COX and PG synthesis pathway.…”
Section: Effects Of Pharmacological Agentssupporting
confidence: 85%
See 1 more Smart Citation
“…They exert their anti-inflammatory effects through the inhibition of endogenous prostaglandins. Similar effects have been reported with black tea, resveratrol, mate tea, orange juice and dark chocolate ( 207 ). Excessive consumption of such foods by the pregnant woman may influence the dynamics of the DA, by inhibiting COX and PG synthesis pathway.…”
Section: Effects Of Pharmacological Agentssupporting
confidence: 85%
“…Similarly, postnatal corticosteroid administration may constrict the ductus ( 206 ). Angiotensin II does not have a role in ductal closure after birth ( 207 ).…”
Section: Effects Of Pharmacological Agentsmentioning
confidence: 99%
“…ATII-R1 inhibits adenylate cyclase, activates phospholipase C, and causes vasoconstriction in other vascular beds (39). However, its role in ductus closure is still in question (40).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II receptors can be one of two types: type 1 and type 2 . A recent study showed that the angiotensin II type 2 receptor, but not the type 1 receptor, played a role in the functional closure of DA . Thus, genetic polymorphisms in AGTR1 might not influence the incidence of PDA in preterm infants.…”
Section: Discussionmentioning
confidence: 99%